2018
DOI: 10.1177/1077546317747501
|View full text |Cite
|
Sign up to set email alerts
|

Vibration response of viscoelastic sandwich plate with magnetorheological fluid core and functionally graded-piezoelectric nanocomposite face sheets

Abstract: In this research, vibration analysis of a viscoelastic sandwich plate rested on a visco-Pasternak foundation is investigated. Sandwich plate consists of a magnetorheological (MR) fluid core and viscoelastic nanocomposite face sheets which include piezoelectric matrix and functionally graded carbon nanotubes (FG-CNTs) fiber. Core and face sheets are affected by applying magnetic and electric fields, respectively. The elastic medium is simulated by a visco-Pasternak model which is considered in terms of the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The first and second letter are related to the top and bottom layers, respectively. The mentioned distribution patterns are related to VCNT* as follow [64,65]:where the negative sign is true for the top and the positive sign is for the bottom face sheets.…”
Section: Formulationmentioning
confidence: 99%
“…The first and second letter are related to the top and bottom layers, respectively. The mentioned distribution patterns are related to VCNT* as follow [64,65]:where the negative sign is true for the top and the positive sign is for the bottom face sheets.…”
Section: Formulationmentioning
confidence: 99%
“…For the MR fluid core, the shear strains can be defined as follows (Ghorbanpour Arani et al, 2018)…”
Section: Theoretical Relationsmentioning
confidence: 99%
“…They appraised the effect of the magnetic field on the alteration of the natural frequencies under different boundary conditions. Also, oscillation response of viscoelastic sandwich plate with MR fluid core and functionally graded piezoelectric nanocomposite face sheets was accomplished by Ghorbanpour Arani et al (2018). They observed that the loss factor, unlike the natural frequency, decreases by enhancing magnetic field severity.…”
Section: Introductionmentioning
confidence: 99%